The Development of an Evidence-Based App to Predict the Need for Enhanced Care for People with Dementia - Sabina London; Shanquan Chen; Emad Sidhom; Christoph Mueller; Benjamin Underwood (BJPsych Open, 2025)
Aims: Dementia is a pressing global health challenge affecting more than 50 million people worldwide with a net impact on the global economy of 1 trillion USD. One aspect of the condition is the potential for deterioration to the point where a crisis situation occurs requiring emergency intense psychiatric support, either in the form of intense community care or admission to an inpatient facility. Such care is only needed for a minority of patients. If patients can be identified at the point of diagnosis, it raises the potential for stratified care pathways for those at highest risk with the aim of improving outcomes. Our previous work from two United Kingdom sites found that younger, male patients, and those with impaired cognition were at risk of deteriorating. In this study, we aimed to create mathematical models of risk and use the results to develop a mobile application that is ready for clinical use.